Efforts of Islamic Religious Teachers to Increase Interest in Reading the Quran in Al Jihad Sunggal Private Madrasah Ibtidaiyah Students - Masithah Ulfah (Education Specialist, 2023)
This study describes the efforts of Islamic religion teachers to increase interest in reading the Al-Qur’an in Al Jihad Sunggal private madrasah ibtidaiyah students. The purpose of this research is to educate and inform the reading public that madrasah ibtidaiyah have a strategic role in increasing interest in reading the Al-Qur’an for students. This type of research is descriptive qualitative using data collection methods, namely observation, unstructured interviews. As for the sources of information in this study, namely, Islamic religious teachers and also some students then data analysis techniques namely data reduction, data presentation and drawing conclusions. Furthermore, in checking the validity of the data, namely using extended observations at the research location. From the research results it was found that first, Islamic religious teachers provide motivation to students in the form of explanations and understanding of how important it is to read the Al-Qur’an for them, especially for their lives in this world and in the hereafter through habituation. Second, Islamic religious teachers synergize with parents of students so that they become role models for students to always read the Al-Qur’an at home. Third, giving awards to students who have fluency in reading the Al-Qur’an so that students are motivated